ADUBAÇÃO NITROGENADA COM UREIA NO DESENVOLVIMENTO INCIAL DA CULTURA DA SOJA - DE MOURA, Daniel Bezerra; GRAICHEN, Felipe André Sganzerla; CAVALCANTI, Vittor Gomes; CEOLIN, Sergio Everton Nascimento; DE MIRANDA, Hevelâyne Cristina Ferreira; ANDRADE, Wagner da Paz (ANAIS DO ENIC, 2017)
-